Toward managing security cost for healthcare information - Hameed, Shihab A.; Yuchoh, Habib (2012)
Medical emergency and healthcare applications holds several sensitive data that requires suitable security techniques to prevent it. Data security, privacy and confidentiality are sample of security used for such applications. To hide those sensitive data from unauthorized accesses, the data need to be encrypted with key which is hold by authorized person. However, adding encryption to the data will increase the degradation in database performance due to: high processing time required of data encrypting and decrypting, the complexity of applying encryption to specific attributes of database, and the cost of key management. This research paper works toward managing the cost of having a suitable security level for sensitive healthcare data. It mainly based on considering multi-level of sensitivity for healthcare data and selecting the suitable encryption method for according to level of sensitivity and volume of data. This leads to eliminate the total processing time for encryption and decryption of whole data and consequently the total cost for security.